Unravelling the unique case of congenital infiltrating lipomatosis of face with its rare associations-A case report - Ramandeep Singh; Aakash Gupta; Gaurav Shanker Pradhan; Arshit Kataria (Elsevier, 2024)
Congenital infiltrating lipomatosis of facial (CIL-F) is a rare tumour of adipose tissue resulting in a progressive craniofacial deformity with involvement of the underlying bones, muscles and joints. We report a very rare case of CIL-F with left sided temporomandibular joint ankylosis in a young patient who presented with facial swelling and reduced mouth opening. This case highlights the imaging features, differential diagnosis and brief management of CIL-F with special emphasis on CT and MRI findings. Also, some associations of CIL-F such as TMJ ankylosis and extraocular muscle hypertrophy has been described, which has been reported very rarely.